2017
DOI: 10.3747/co.24.3782
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Patients with Cancer during Diagnosis and Treatment Planning: A Descriptive Study of Canadian Survey Results

Abstract: Background Communication with health care providers during diagnosis and treatment planning is of special

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
(17 reference statements)
2
19
0
Order By: Relevance
“…In addition, Myeloma patients reported longer times waiting for a diagnosis than the average for all other cancers and were less likely to feel that they received the information they needed about the tests and subsequent diagnosis. Coronado et al., 2017 39 The experience of patients with cancer during diagnosis and treatment planning: a descriptive study of Canadian survey results A cross-sectional study using the AOPSS data in Canada for all cancer patients included in the survey between 2012 and 2016 To examine variation in patients’ experiences with patient-provider communication, during the diagnosis and treatment planning phases of cancer care 1 This study showed variation in patients’ experiences with patient-provider communication. Most respondents (92%) reported that their care provider told them of their cancer diagnosis in a sensitive manner and felt that they were provided with enough information about their cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Myeloma patients reported longer times waiting for a diagnosis than the average for all other cancers and were less likely to feel that they received the information they needed about the tests and subsequent diagnosis. Coronado et al., 2017 39 The experience of patients with cancer during diagnosis and treatment planning: a descriptive study of Canadian survey results A cross-sectional study using the AOPSS data in Canada for all cancer patients included in the survey between 2012 and 2016 To examine variation in patients’ experiences with patient-provider communication, during the diagnosis and treatment planning phases of cancer care 1 This study showed variation in patients’ experiences with patient-provider communication. Most respondents (92%) reported that their care provider told them of their cancer diagnosis in a sensitive manner and felt that they were provided with enough information about their cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients with prostate cancer tend to report the worst experiences of being referred for emotional support in Canada. 39 In terms of experience with cancer diagnosis, patients who were diagnosed with late stage disease were more likely to report worse care experiences in England, 40 and in the USA. 41 , 42 , 43 Moreover, patients with multiple myeloma and pancreatic cancer were more likely to report negative experiences in England, 19 , 44 while patients with thyroid, vulvar, and multiple myeloma cancers were more likely to report negative experiences in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to study the quality of the attention process during dying and death, but not the quality of the experience itself Thank you for these insightful comments and I agree there are issues around how to collect and analyse patient experience. However, nursing research is primarily about studying the quality of the patient experience as explored in the following articles: (Brady, 2012, Coronado et al, 2017, Day et al, 2015, Embrey, 2008, Kamal et al, 2018, Matthews and Cornwell, 2012, Parra et al, 2017, Taylor, 2011, Thomas et al, 2017, These articles are based on the premise that studying the quality of the patient experience can improve care. It is impossible to study the quality of the patient experience after death, (because the patients aren't there to ask) hence the carers, both formal and informal act as surrogates for the patient.…”
Section: Reviewer 3 Commentsmentioning
confidence: 99%
“…The Beryl institute defines patient-reported experience as the sum of interactions, shaped by an organization’s culture, that influence patient perceptions across the continuum of care [ 6 ]. Given that quality of care is not only assessed by success in the technical aspects of medical procedures but also by measuring the way that healthcare services were delivered, there has been growing interest in including experience measures in quality improvement (QI) initiatives [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%